2005
DOI: 10.1002/dvdy.20489
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of gene expression during epithelial–mesenchymal transformation

Abstract: One of the most fundamental biological processes in development, as well as a primary mechanism for tumor metastasis, is epithelial-mesenchymal transformation (EMT). To gain a greater understanding of this transition, we have obtained a genomic profile of the critical stages before and during this rapid change in morphology in the developing mouse palate. By isolating the medial edge epithelium of each palatal shelf, we were able to obtain pure gene expression data without contamination from surrounding mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 35 publications
3
80
1
Order By: Relevance
“…Complex gene-expression changes are characteristic for the EMT program and epithelial and mesenchymal cells can be distinguished by expression of a number of classical markers used for defining either epithelial or mesenchymal cells (29). Classical epithelial markers include adherence and tight-junction proteins such as E-cadherin and ZO-1, whereas the mesenchymal counterparts are frequently characterized by N-cadherin, fibronectin and vimentin (30).…”
Section: Epithelial To Mesenchymal Transition (Emt)mentioning
confidence: 99%
“…Complex gene-expression changes are characteristic for the EMT program and epithelial and mesenchymal cells can be distinguished by expression of a number of classical markers used for defining either epithelial or mesenchymal cells (29). Classical epithelial markers include adherence and tight-junction proteins such as E-cadherin and ZO-1, whereas the mesenchymal counterparts are frequently characterized by N-cadherin, fibronectin and vimentin (30).…”
Section: Epithelial To Mesenchymal Transition (Emt)mentioning
confidence: 99%
“…Using a published procedure (LaGamba et al, 2005) palatal shelves were dissected from E14.5 Adamts9 +/-;bt/bt embryos (n4) and placed on the surface of a 0.9% agarose gel in DMEM/F12 supplemented with 10% fetal bovine serum (FBS) and antibiotics (100 U/ml penicillin and 100 mg/ml streptomycin), with their medial edge epithelia in contact. The medium was replaced daily.…”
Section: Palatal Shelf Organ Culturementioning
confidence: 99%
“…In the 4T1 and the MDA-MB-231 tumor models, systemic administration of a soluble TbRII protein or dominant negative TbRII overexpression, respectively, displayed anti-metastatic effects (Yin et al, 1999;Muraoka et al, 2002). Several studies have provided evidence that Smad2 and Smad3 have different transcriptional functions and profiling studies have revealed distinct target genes for Smad2 and Smad3 (Kretschmer et al, 2003;LaGamba et al, 2005;Dzwonek et al, 2009). In addition, although mice deficient in Smad2 are embryonic lethal, Smad3-deficient mice are viable (Weinstein et al, 1998;Ashcroft et al, 1999;Yang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%